Pembuatan dan Pemanfaatan Busy Book dalam Mempercepat Kemampuan Membaca untuk Anak Usia Dini di Paud Budi Luhur Padang - Ulfah, Azra Aulia; Rahmah, Elva (Ilmu Informasi Perpustakaan dan Kearsipan, 2017)
The purpose of this paper was to describe the stages of designing and utilizing â€œBusy Bookâ€ in accelerating the beginning reading ability for early childhood children at PAUD Budi Luhur Padang. This paper was written by using descriptive qualitative method. The data were collected through observation, interview, and literature study. It is concluded that the stages in designing â€œBusy Bookâ€ were, (1) first, determining the concept, and the number of pages; (2) after that cutting the flannel; (3) designing the background of â€œBusy Bookâ€ pages (4) each edge of the background was decorated with ribbons; (5) creating the desired pattern; (6) then copying the pattern on the flannel and cutting it according to the pattern; (7) preparing the object background of each page in â€œBusy Bookâ€; (8) the object was attached; (9) naming the image by writing the letters on the flannel; (10) pasting the letters of the flannel on the velcro that has been glued on the background adjusted to the object; (11) making front and back cover of â€œBusy Bookâ€. The utilization of â€œBusy Bookâ€ at PAUD Budi Luhur Padang could be categorized as good. There was the desire of students to hold the book, to ask to get the book read, to mention the name of the picture. When students read the pictures on every page of the book and told the self-made pictures could be categorized as fairly good for early childhood children in learning to read at the beginning. However, students could not yet be able to mention the function based on the picture.Keyword: busy book, early childhood, read.